The Myth of the Emperor and the Yamato Race: The Role of the Tairiku nippô in the Promotion of Japanese-Canadian Transnational Ethnic Identity in the 1920s and the 1930s - Fujiwara, Aya (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2010)
This article examines the role that the Japanese-Canadian (first-generation) issei press, the Tairiku nippô, played in transnational ethno-racial identity, focusing on the myths of the Emperor and the Yamato race. The newspaper is an invaluable source that shows Japanese Canadians’ self-image that emerged in response to intense anti-Asianism in British Columbia during the 1920 and the 1930s. The press incorporated politicized images and stories, which integrated  the Emperor and Japanese racial roots into its editorials and columns, boosting their sense of racial pride. Hirohito’s daijôsai of 1928 and Japan’s invasion of the Manchuria in 1931 served as the best opportunities to spread their myths and symbols. The newspaper also became a space where Japanese Canadians could freely express their opinions and feelings for their homeland through essays and poems, without facing any criticisms from mainstream British Columbians. An examination of such messages reveals that Japanese-Canadian Buddhist issei, and some nisei, who had strong affiliation with the Tairiku nippô, maintained their loyalty to the Emperor, and expanded the idea that they were part of the noble Yamato race. Their ideology was a factor that prompted them to support and justify Japan’s invasion of China.